Rehabilitation Management of Post Palatoplasty in Adolescent: Case Report - Dewi Kusuma Hartono (Faculty of Medicine, Universitas Airlangga, 2021)
The objective of this study is to report comprehensive physical medicine and rehabilitation management of post-palatoplasty in an adolescent patient. The cleft palate repair is usually done in the first year of life in order to gain optimal speech function. To achieve normal communication development, normal hearing, normal oral and pharyngeal structures, adequate stimulation, and reinforcement from the environment for communication efforts are needed. Patient was assessed comprehensively using The International Classification of Functioning, Disability and Health (ICF) and by perceptual assessment for speech. The results showed that after one month intervention, the perceptions of hypernasality in plosive /b/ and affricates /c/ were found reduced significantly. There was improvement in articulation after one month of intervention.